2017
DOI: 10.1007/s00592-017-1023-9
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic exercise for adults with type 2 diabetes: a meta-analysis

Abstract: A1c can be reduced after eight-twelve weeks of AquaEx. However, at this time few studies have examined whether changes in A1c are different from LandEx or Crtl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…A systematic review and meta-analysis found higher frequency of regular leisuretime physical activity was more effective in reducing A1C levels (191). A wide range of activities, including yoga, tai chi, and other types, can have significant impacts on A1C, flexibility, muscle strength, and balance (167,(192)(193)(194). Flexibility and balance exercises may be particularly important in older adults with diabetes to maintain range of motion, strength, and balance (177).…”
Section: Frequency and Type Of Physical Activitymentioning
confidence: 99%
“…A systematic review and meta-analysis found higher frequency of regular leisuretime physical activity was more effective in reducing A1C levels (191). A wide range of activities, including yoga, tai chi, and other types, can have significant impacts on A1C, flexibility, muscle strength, and balance (167,(192)(193)(194). Flexibility and balance exercises may be particularly important in older adults with diabetes to maintain range of motion, strength, and balance (177).…”
Section: Frequency and Type Of Physical Activitymentioning
confidence: 99%
“…Since osteoarthritis can be a barrier to physical activity (52), water-based physical activities, such as swimming, walking or running in a pool, or aquatic fitness classes have been encouraged for people with such comorbidities (53,54). While few highquality trials exist, a recent meta-analysis suggests aquatic exercise improves A1C compared to no exercise comparison groups and that the improvements are comparable to those obtained with landbased exercise (55).…”
Section: Benefits Of Other Types Of Exercisementioning
confidence: 99%
“…Recent investigations in people with DM and cardiovascular disease have reported beneficial effects following unconventional forms of exercise, such as aquatic-based exercise, Nordic walking, specific gym-fitness activities, Yoga, Pilates, Tai Chi, and dance-based activities. Less common approaches have been shown to induce positive cardiovascular effects, also improving general well-being, social inclusion, and quality of life of the participants [141][142][143][144][145][146][147].…”
Section: Exercise As Therapy For Diabetes Mellitus: Unconventional Anmentioning
confidence: 99%